2012
DOI: 10.1111/j.1464-410x.2012.11591.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between overactive bladder and irritable bowel syndrome: a large‐scale internet survey in Japan using the overactive bladder symptom score and Rome III criteria

Abstract: What's known on the subject? and What does the study add?There is known to be an association between overactive bladder (OAB) and irritable bowel syndrome (IBS).The study investigates the association between OAB and IBS using an internet-based survey in Japan. It is the first to investigate the prevalence and severity of OAB in the general population using the OAB symptom score questionnaire.ObjectiveTo investigate the association between overactive bladder (OAB) and irritable bowel syndrome (IBS) by using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 28 publications
(43 reference statements)
2
46
0
Order By: Relevance
“…In most Western countries, IBS affects more women (60%-70%) than men[42,43]. The prevalence of IBS in this study was 64.8% in females, which was similar to Western countries but higher than some Asian countries, such as India (59.69%)[44], and Japan(50%)[45]. Some previous studies in China had reported the prevalence of IBS in female patients as 56.50% in Shanghai[46], and 55.56% in Guangdong province[47].…”
Section: Discussionsupporting
confidence: 55%
“…In most Western countries, IBS affects more women (60%-70%) than men[42,43]. The prevalence of IBS in this study was 64.8% in females, which was similar to Western countries but higher than some Asian countries, such as India (59.69%)[44], and Japan(50%)[45]. Some previous studies in China had reported the prevalence of IBS in female patients as 56.50% in Shanghai[46], and 55.56% in Guangdong province[47].…”
Section: Discussionsupporting
confidence: 55%
“…Higher OAB prevalence among women than men has been reported in Korea . In contrast, other Asian studies suggest a higher prevalence of OAB in men . Differences between study populations with regard to age may have contributed to these findings.…”
Section: Discussionmentioning
confidence: 71%
“…Various reports in the literature suggest the existence of overlap between OAB and some of the more commonly recognized central sensitization syndromes 36,41 , including IBS 77,92,94,120,121 , fibromyalgia 122–126 , and idiopathic back pain 127 . According to population data, over one-third of Japanese women with OAB have concomitant IBS, as defined by Rome criteria 128 , whereas American women are more likely to report a diagnosis of IBS if they have more severe storage-type lower urinary tract symptoms 120 . Women with IBS are also more likely to report storage-type lower urinary tract symptoms of greater severity than those without IBS 82 .…”
Section: Current Evidencementioning
confidence: 99%